syofiah ANALISIS PEMANFAATAN MEDIA SOSIAL SEBAGAI STRATEGI PROMOSI DAN PEMASARAN DALAM BERWIRAUSAHA: ANALISIS PEMANFAATAN MEDIA SOSIAL SEBAGAI STRATEGI PROMOSI DAN PEMASARAN DALAM BERWIRAUSAHA - syofiah (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2022)
Home business is one type of micro and small business (MSME) which is seen from its economic scale which is still low but is able to become one of the important parts in the economy of a country with the number of home businesses currently very large and dominant. The purpose of this study was to find out and analyze the use of social media as a promotion and marketing strategy by the